The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acsphotonics.3c00466
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Two-Dimensional Exciton Propagation via Strong Light–Matter Coupling with Surface Lattice Plasmons

Abstract: Exciton−polaritons�hybrid exciton−photon quasi-particles�have enabled exciting long-range coherent transport by taking advantage of the properties of their photonic component. However, most experimental demonstrations of strong coupling have been based on semiconductor Fabry−Peŕot microcavities. Here, we report an open and versatile exciton−polariton platform by integrating two-dimensional lead halide perovskites with plasmonic nanoparticle arrays, which support hybridization between excitons and surface latti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…In the results Section , we choose the MNP and PC parameters to maximize the optical near-field of the PC, such that both resonances appear for the same frequency range. In this case, the collective interactions do not cause a narrow distinct peak, as focused on, e.g., in refs , , , but rather amplify and sharpen the present MNP resonance.…”
Section: Theoretical Modelsupporting
confidence: 55%
See 1 more Smart Citation
“…In the results Section , we choose the MNP and PC parameters to maximize the optical near-field of the PC, such that both resonances appear for the same frequency range. In this case, the collective interactions do not cause a narrow distinct peak, as focused on, e.g., in refs , , , but rather amplify and sharpen the present MNP resonance.…”
Section: Theoretical Modelsupporting
confidence: 55%
“…Its distance dependency is depicted in the inset of Figure b, illustrating the (δ z ) −2 proportionality. To assign the hybrids to a particular coupling regime, the effective Rabi energy Ω eff ≠ 0 is compared with the line width γ ex and γ pl of the individual constituents. , A coupling strength leading to a peak splitting that is small compared to the line widths as, e.g., in the δ z = 17 nm , case is still assigned to weak coupling and has been observed in experiments with TMDCs coupled to a MNP or a PC in refs , , , and .…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…This has mostly been demonstrated in steady-state measurements, 119,153,156 though there are limited reports of time-resolved studies focusing on such energy transport in Fabry-P erot cavities, BSWPs, and even cavity-free polaritons. 104,139,147,[157][158][159] Yet, the choice of materials, methods of characterization, and cavity architectures are sufficiently scattered that it remains unclear how to control these effects, and the field is in need of systematic investigations to understand the mechanisms underpinning polariton transport. Numerous steady-state studies have highlighted the potential of polariton-assisted energy transfer, with reported distances reaching up to 100's of micrometers.…”
Section: A Lateral Transport: Diffusive To Ballisticmentioning
confidence: 99%
“…However, a recently published set of time-resolved studies reveals a much more complicated picture. 104,139,147,[157][158][159] In each case, the polariton-assisted energy transport was studied using some variation of pump-probe microscopy (Fig. 12).…”
Section: A Lateral Transport: Diffusive To Ballisticmentioning
confidence: 99%
See 1 more Smart Citation